Perception of Junior High School Students about the Use of E-books as Learning Sources - Aufal Hadaya; Asrowi Asrowi; Sunardi Sunardi (Universitas Negeri Makassar, 2018)
This study aims to determine the perception of junior high school students about e-books as a learning source. This study used survey method involving 95 junior high school students. The questionnaire is used to find out the students' perceptions of e-books. The results show that although today's students have been familiar with many technologies, including handheld devices, however, evidently they do not fully involve technology for their learning activities. In fact, there are still many students who prefer to use conventional printed books rather than electronic books. This study also revealed several reasons for their preference, their reason can be a consideration for learning developers to design e-books that match the characteristics, expectations, and needs of students.